Comparison of Cyperus papyrus Planting Media Combinations in Heavy Metal Removal Using a Subsurface Flow Wetland System with Aeration Pretreatment - Era Dinisiadela; Aussie Amalia; Syadzadhiya Qothrunada Zakiyayasin Nisa (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The electroplating industry generates wastewater containing hazardous heavy metals such as copper (Cu) and nickel (Ni), which can contaminate aquatic and terrestrial environments. Initial tests showed Cu and Ni concentrations of 92.6 mg/L and 76.23 mg/L, respectively—far exceeding the permissible limits. To address this issue, an environmentally friendly treatment technology was employed, using a subsurface-flow constructed wetland planted with Cyperus papyrus. The study used combinations of soil and rice husk biochar media at weight ratios of 1:0, 1:1, 1:2, and 2:1. Aeration pretreatment was conducted for 24 hours before wastewater was introduced into the subsurface flow wetland. The hydraulic retention times were 0, 5, 10, and 15 days. The results indicated that the 2:1 media combination under aerated conditions achieved the highest removal efficiencies—93.02% for Cu and 96.81% for Ni on the 15th day. Plant tissue analysis revealed the highest metal accumulation in the roots, with Cu and Ni contents of 0.315 mg/g and 0.241 mg/g, respectively. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land The electroplating industry generates wastewater containing hazardous heavy metals such as copper (Cu) and nickel (Ni), which can contaminate aquatic and terrestrial environments. Initial tests showed Cu and Ni concentrations of 92.6 mg/L and 76.23 mg/L, respectively—far exceeding the permissible limits. To address this issue, an environmentally friendly treatment technology was employed, using a subsurface-flow constructed wetland planted with Cyperus papyrus. The study used combinations of soil and rice husk biochar media at weight ratios of 1:0, 1:1, 1:2, and 2:1. Aeration pretreatment was conducted for 24 hours before wastewater was introduced into the subsurface flow wetland. The hydraulic retention times were 0, 5, 10, and 15 days. The results indicated that the 2:1 media combination under aerated conditions achieved the highest removal efficiencies—93.02% for Cu and 96.81% for Ni on the 15th day. Plant tissue analysis revealed the highest metal accumulation in the roots, with Cu and Ni contents of 0.315 mg/g and 0.241 mg/g, respectively. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land